2007
DOI: 10.1093/ps/86.2.282
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Low-Density Broiler Breeder Diets on Performance and Immune Status of their Offspring

Abstract: Effects of low-density broiler breeder diets on offspring performance and mortality were studied using 2,100 female and 210 male Cobb 500 breeders. Breeder treatments involved 4 experimental groups and a control group with normal density diets (ND, 2,600 kcal of AME/kg during rearing and 2,800 kcal of AME/kg during laying). In treatment 2, nutrient densities were decreased by 12% (LD12) and 11% (LD11) during the rearing and laying periods, respectively, whereas in treatment 3, nutrient densities were decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 29 publications
2
13
0
1
Order By: Relevance
“…These findings were confirmed in an experiment of Zuidhof et al (1995), who observed an improved feed and crude protein conversion efficiency in broiler breeder layers that were fed a diet diluted with 15% ground oat hulls compared to hens fed an undiluted diet. Low-density broiler breeder diets were found to improve offspring growth rates, reduce mortality, and reduce or increase immune responses, depending on breeder age and egg weight (Enting et al, 2007a). These positive results, however, were only found in the 15% diluted diet and not in a 30% diluted diet (Zuidhof et al, 1995).…”
Section: Side Effects Of Dietary Dilution and Fibre Additionmentioning
confidence: 97%
“…These findings were confirmed in an experiment of Zuidhof et al (1995), who observed an improved feed and crude protein conversion efficiency in broiler breeder layers that were fed a diet diluted with 15% ground oat hulls compared to hens fed an undiluted diet. Low-density broiler breeder diets were found to improve offspring growth rates, reduce mortality, and reduce or increase immune responses, depending on breeder age and egg weight (Enting et al, 2007a). These positive results, however, were only found in the 15% diluted diet and not in a 30% diluted diet (Zuidhof et al, 1995).…”
Section: Side Effects Of Dietary Dilution and Fibre Additionmentioning
confidence: 97%
“…Due to different size preferences, egg consumption is highly diverse around the world [e.g., many consumers prefer relatively large eggs in some Western countries, as opposed to China (Jones et al, 2001;Koelkebeck et al, 2001)]. Moreover, egg weight has been reported to have a crucial effect on chick quality including hatchability, hatch weight, fitness, and chick performance (Pinchasov, 1991;Hart-mann et al, 2003;Enting et al, 2007;Nangsuay et al, 2011). Therefore, producing eggs of appropriate size and weight is a key issue for both producers and breeders.…”
Section: Introductionmentioning
confidence: 99%
“…However, given the inconsistent results of several studies, this concern may or may not be justified. Some studies show no effect (Puthpongsiriporn and Scheideler, , Bautista‐Ortega et al., ), some show a detrimental effect (Pappas et al., ; Al‐Khalifa et al., ), and some show an improvement (Wang et al., ; Yang and Guo, ; Enting et al., ). In our study, the inclusion level of 3.0% was probably too high, thereby provoking negative effects.…”
Section: Discussionmentioning
confidence: 99%